Powassan Virus—A New Reemerging Tick-Borne Disease - Fatmi, Syed Soheb; Zehra, Rija; Carpenter, David O. (Frontiers in Public Health, 2017)
Powassan virus is a neurovirulent flavivirus consisting of two lineages causing meningoencephalitis. It is the only member of the tick-borne encephalitis serogroup which is present in mainland North America. With a total number of 27 cases from 1958 to 1998 and 98 cases from 1999 to 2016, reported cases have increased by 671% over the last 18 years. Powassan infection is transmitted by different tick species in different geographical regions. Ixodes scapularis is the primary vector that transmits the virus on the East Coast of US and Ixodes cookei in the Midwest and Canada, while Hemaphysalis longicornis is the vector in Russia. Powassan has no singular pathognomonic finding and presents with a wide spectrum of symptoms including severe neurological symptoms. The clinical challenge lies within the management of the disease as there is no standard diagnostic protocol and most cases are only diagnosed after a patient goes through an extensive workup for other infectious disease. The diagnosis is established by a combination of imaging and serologic tests. In case of Powassan meningoencephalitis, computed tomography scan and magnetic resonance imaging show vascular insults, which are also seen in cases of tick-borne encephalitis virus, another flavivirus of medical importance. Serologic tests are the gold standard for diagnosis, although testing is not widely available and only state health departments and Center for Disease Control and Prevention can perform Powassan-specific IgM antibody testing utilizing enzyme-linked immunosorbent assay and immunofluorescence antibody. Powassan is also of veterinary medical importance. Wildlife animals act as a reservoir to the pathogens, hence possessing threat to humans and domestic animals. This review highlights Powassan’s neurotropic presentation, epidemiology, diagnostic challenges, and prevalence. Strong emphasis is placed on establishing diagnostic protocols, widespread Powassan-specific IgM testing, role of the vector in disease presentation, and necessary preventive research.